Multiracial Church Attendance and Support for Same‐Sex Romantic and Family Relationships. Issue 2 (26th February 2013) - Perry, Samuel L.
<x xml:space="preserve">Abstract</x> Research has found that attending a racially diverse congregation promotes more favorable attitudes toward interracial dating, marriage, and adoption, but does participation in an integrated faith community promote tolerance toward other non‐traditional romantic and family forms? This study examines the relationship between involvement in a racially diverse congregation and support for same‐sex romantic and family relationships. Data are taken from the 2005 Baylor Religion Survey. I fit logistic regression models to estimate the effect of attending a multiracial church on support for homosexuality, same‐sex marriage, and same‐sex adoption, net of sociodemographic and religious controls. Results indicate that persons who attend churches where between 25 and 75 percent of attendees are of another race are more likely to support gay sex, marriage, and adoption compared with those who attend more racially homogenous churches. This relationship generally holds when models are estimated for evangelicals and mainline Protestants separately, but not for Catholics. Findings suggest a link between religion‐based racial prejudice and heterosexism/homophobia and that increased exposure to racial diversity may promote a general tolerance toward non‐traditional romantic couples and families.